THE PROBLEMS ASSOCIATED WITH SWITCHING BRAND-NAME ANTIEPILEPTIC DRUGS TO GENERICS: A FOCUS ON TOPAMAX: A REVIEW OF LITERATURE AND A CASE REPORT - K. Yu. Mukhin; O. A. Pylaeva; M. Yu. Bobylova (Русский журнал детской неврологии, 2016)
Despite the rather high efficiency of treatment for epilepsy (overall, 65–70 % of patients can achieve remission or show a considerable decrease in the frequency of seizures), there remains a challenge due to the need to use antiepileptic drugs long and regularly: therapy adherence, compliance, treatment tolerability, and impact of therapy on quality of patent’s life. One of the aspects of this problem is a very common tendency to switch brand-name antiepileptic drugs to their generics that are 1ess expensive, but also less predictably effective and tolerable. The authors review the literature on the interchangeability of brand-name and generic drugs and describe their case.